Lethal and sub lethal effects of Metarhizium anisopliae against Spodoptera litura - Sowmya, G; Ramanagouda, S H; Jayappa, J (Indian Journal of Plant Protection, 2020)
The effect of Metarhizium anisopliae was determined against Spodoptera litura by leaf dip method. A total of three isolates (SSB, SBvB and SBvD) of M. anisopliae from 60 samples soil and insect samples were obtained based on their pathogenicity test against S. litura. Among the three isolates, SSB (76.67 %) and SBvB (63.33 %) showed highest mortality whereas the least mortality was found in the isolate SBvD (50.00 %) at six days after treatment at the concentration of 3x 108 cfu/1000 ml. Further, sub lethal effect were also studied and showed that, the per cent pupation, adult emergence and fecundity (23.33, 6.67, 0.00, respectively) were very poor in the SSB isolate depicting the high virulence whereas SBvB isolate recorded 50.00, 23.33, 23.00 per cent, respectively indicating poor virulence. The order of mortality and sub lethal effect of these isolates were SSB>SBvB>SBvD. These isolates performed better under laboratory conditions and need to be evaluated under field conditions for their promotion against soil dwelling and defoliating insect pests of this geographical area